(untitled) (International relations and international law Journal, 2022)
Climate change makes and shapes the globalized world in important ways. As the COVID-19 pandemic brings the health of the human race and the health of the Earth to the forefront of world politics, urgent action to combat climate change and its impacts has been called for. Given the pledge of President Kassym-Jomart Tokayev that Kazakhstan is to reach carbon neutrality by 2060, this research paper aims to investigate the Republic’s domestic and international climate ambitions with specific attention paid on the national development project “Green Kazakhstan.” The research question is: to what extent are Kazakhstan’s domestic and international climate ambitions complementary, or disparate? Constructivism is employed as the theoretical framework to unveil the domestic challenges faced by President Tokayev to pursue a low-carbon transition in referral to Kazakhstan’s latest foreign policy concept, supplemented by the use of quantitative results produced by the Climate Change Performance Index and the Global Carbon Project to assess the Republic’s capability and responsibility to display a climate ambition. The findings indicate that Kazakhstan’s domestic and international climate ambitions are considered disparate on most occasions but nonetheless have undeniable domestic and international significance. Key words: Kazakhstan; capability; climate; emissions; energy; environment; green; responsibility